English phrasal verbs: usage, knowledge, acquisition - Garnier, Mélodie (2016)
Formulaic language constitutes an essential part of English vocabulary and is necessary for performing a wide range of communicative functions, but knowledge and acquisition of formulaic sequences is typically found to be lacking and problematic for L2 learners. Whilst much research has been carried out on formulaic sequences such as idioms and collocations, comparatively little has been done on phrasal verbs which are nonetheless commonly perceived as one of the most challenging aspects of English vocabulary. This thesis attempts to contribute to filling this gap by exploring the usage, knowledge and acquisition of phrasal verbs by native and non-native speakers of English.